Blockchain Technology: Architectures, Security Challenges, and Emerging Applications (International Journal of Advanced Digital Systems and Multidisciplinary Studies, 2026)
This paper presents a comprehensive review of blockchain technology, encompassing its fundamental architectural designs, prevalent security challenges, and burgeoning application domains. It delineates the intricate layered structure of blockchain, providing a foundational framework for understanding its operational complexities and vulnerabilities. Furthermore, it explores how various security threats can undermine the integrity and reliability of blockchain systems, offering a novel taxonomy for classifying existing research on vulnerability detection within this rapidly evolving technological landscape. It also provides an in-depth analysis of prominent attack vectors encountered within the blockchain ecosystem, accompanied by an exploration of existing defense mechanisms and a discussion of future research directions to enhance system robustness. This comprehensive analysis aims to dissect the intricate ecosystem of blockchain, offering readers a nuanced understanding of its multifaceted security landscape.
Keywords: Blockchain, distributed ledger technology, cryptography, consensus algorithms, security, attacks, vulnerabilities, applications.